D-Branes - Johnson, Clifford V. (Cambridge University Press, 2003)
D-branes represent a key theoretical tool in the understanding of strongly coupled superstring theory and M-theory. They have led to many striking discoveries, including the precise microphysics underlying the thermodynamic behaviour of certain black holes, and remarkable holographic dualities between large-N gauge theories and gravity. This book provides a self-contained introduction to the technology of D-branes, presenting their development in a pedagogical manner. The introductory material is developed by first starting with the main features of string theory needed to get rapidly to grips with D-branes. Many advanced applications are covered, with discussions of open problems which could form the basis for other avenues of research. Suitable as a textbook in graduate courses on modern string theory and theoretical particle physics, it will also be an indispensable reference for seasoned practitioners.